Soil heterogeneity and plant species diversity in experimental grassland communities: contrasting effects of soil nutrients and pH at different spatial scales - Xue, Wei; Bezemer, T. Martijn; Berendse, Frank (Plant and soil, 2019)
Background and aims Current knowledge of soil heterogeneity-diversity relationships (HDR) is largely based on studies manipulating single factor, but the advancements in HDR may require a comprehensive experiment incorporating multiple factors. Methods We conducted a three-year field experiment in which a seed mixture of 16 common grassland species was sown in plots with heterogeneous soils consisting of small (10 cm × 10 cm) or large patches (30 cm × 30 cm) of low and high nutrients or low and high pH, and homogeneous soils with an even mixture of low and high nutrient/pH soils. Soil nutrients and pH were manipulated in separate treatments. We determined plant species richness and diversity at two focal scales (40 cm × 40 cm plot-scale and 10 cm × 10 cm patch-scale). Results Plot-scale richness and diversity were not influenced by soil heterogeneity, but patch-scale richness was lower in plots with heterogeneous nutrients than in plots where nutrients were distributed homogeneously. There was no difference between the two heterogeneous nutrient soils with different grain sizes. Patch-scale diversity was higher in heterogeneous pH soils of large patch size than in heterogeneous pH soils of small patch size or the homogeneous pH soil at the final harvest. Species richness and diversity quantified at both plot and patch scales declined in all soils over time. Conclusions The influence of soil heterogeneity on plant species diversity depends on whether the soil varies in nutrients or pH, and on the temporal-spatial scale at which species diversity and soil heterogeneity are measured. These results indicate that soil heterogeneity has the potential to promote plant coexistence and future HDR studies should consider multiple soil factors at various temporal-spatial scales.